Control of temporary employment agencies employing the posted employees - Kiełbowicz-Dziwulska, Agnieszka (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
Article presents the principles for performing the control of social contribution payers and analysis of atypical forms of employment within the range of employment provided via private temporary employment agencies, with particular regard to seconded workers, assigned to perform the work abroad. The growing number of civil-law contracts and registered private temporary employment agencies indicate the need for increasing flexibility on the labour market. The study presents the scale of the phenomenon, as well as the analysis of the causes of the changes taking place. The trend of a deepening diversity of forms of employment precedes legislative changes in relation to the provisions governing the social security system, not only in Poland, but also in the provisions of EU law. As a consequence, market changes and legal provisions that are not adapted to them often cause misunderstanding, and may also be a potential source of abuse in the field of social security. The issue was presented from the perspective of the control of payers of contributions carried out by the Social Insurance Institution, in particular the rights of inspectors of the Inspection of the Institution and the obligations of payers of contributions specified in the provisions of the Act on the social insurance system. The author presents potential examples of irregularities that can be disclosed as a result of control of activity of private temporary employment agencies on example of seconded employees as well as financial consequences in aspect of obligation to pay the social contributions, including negative consequences for the course of insurance of the employed persons.